(untitled) (Asian Journal of Medical and Biological Research, 2023)
Campylobacter is a prevalent zoonotic bacterial pathogen found in various food animals such as cattle, sheep, goats, and poultry. The increasing production of crossbred cattle in Bangladesh is aimed at meeting the demand for animal protein. However, this trend also poses public health risks associated with emergence of cattle-specific Campylobacter. It is probable that there is an increased probability of transmission of pathogenic Campylobacter among humans and animals, as well as within the farm environment. Nevertheless, it has been established that Campylobacter is also a significant contributor to childhood diarrhea in Bangladesh. The objective of this study is to examine Campylobacter in animals and humans, including the risk factors that contribute to its occurrence, patterns of antimicrobial resistance, and measures that can be taken to prevent and control its spread. The study has established predominant maintenance zoonotic Campylobacter in source animals and their burden in humans is enormous. Our research is primarily focused on promoting public health by improving cleaning and sanitation practices in animal farms, which can help reduce the amount of Campylobacter present in the environment. The data and insights provided in this article can be valuable for policy planners and public health experts who are working to create effective and sustainable strategies aimed at reducing the risks associated with Campylobacter infection over the long term. Asian J. Med. Biol. Res. 2023, 9 (2), 38-50